THE ICP-MS DETERMINATION OF RARE EARTHS AND OTHER METALS IN BAIKAL CRUDE OIL: COMPARISON WITH CRUDE OILS IN SIBERIA AND THE RUSSIAN FAR EAST - Yasnygina T.A.; Malykh Yu.M.; Rasskazov S.V.; Primina S.P.; Zemskaya T.I.; Khlystov O.M. (My University, 2006)
Hydrocarbon shows were already known half a century ago on the eastern coast of Lake Baikal. Zamaraev and Samsonov studied crude oils in the Klyuchi–Tolstyi Cape area and concluded that Tertiary sediments have the highest crude oil potential. Based on findings of Sinian spores in the crude oils, M.M. Mandel’baum et al. assumed that they are related to deep Precambrian rocks. However, new data obtained by A.E. Kontorovich et al. suggest that aliphatic hydrocarbons of Baikalian crude oil lack 12- and 13-methylalkanes that are typical of ancient crude oils in the Siberian Craton.